A Critical Multimodal Analysis of Text and Images in Roald Dahls Matilda and The Witches - Surya, Nobel Dilavenna; Nurhadi, Muljani Ahmad; Musliman, Acep (INFERENCE: Journal of English Language Teaching, 2024)
This thesis investigates the multimodal analysis of text and illustrations in Roald Dahl’s Matilda and The Witches. It explores the relationship between text and illustrations in constructing themes, characters, and narrative experience, using a multimodal framework based on representational, interactional, and compositional meanings. The findings reveal that illustrations in both novels significantly enhance the narrative. In Matilda, they emphasize Matilda’s intelligence, power, and resilience while highlighting her parents’ oppressive behavior. In The Witches, illustrations intensify danger and fear through grotesque depictions of the witches. Both novels demonstrate the synergy between text and illustrations in creating emotional impact, clarifying themes, and enriching the reading experience. This study underscores the importance of illustrations in children’s literature as tools that contribute meaningfully to readers’ understanding, rather than mere decorative elements.